2005
DOI: 10.1079/phn2005666
|View full text |Cite
|
Sign up to set email alerts
|

Consumer understanding and use of nutrition labelling: a systematic review

Abstract: Improvements in nutrition labelling could make a small but important contribution towards making the existing point-of-purchase environment more conducive to the selection of healthy choices. In particular, interpretational aids can help consumers assess the nutrient contribution of specific foods to the overall diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
314
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 722 publications
(343 citation statements)
references
References 18 publications
25
314
0
4
Order By: Relevance
“…Noussair et al (2002) found that European consumers typically remained unaware of labelling regarding foods containing genetically modified ingredients. Recent reviews of food labelling suggest that consumers make relatively little use of nutrition information, particularly if the information is complicated (Cowburn and Stockley 2005;Grunert and Wills 2007;Rex and Baumann 2007). Many researchers (e.g., Erskine and Collins 1997;Valor 2008;Weightman and McDonagh 2004) have reported that consumers are rarely influenced by claims of sustainability, but others have reported an increasing willingness to pay a premium for "green" products (Laroche et al 2001;Young et al 2010).…”
Section: Literaturementioning
confidence: 96%
“…Noussair et al (2002) found that European consumers typically remained unaware of labelling regarding foods containing genetically modified ingredients. Recent reviews of food labelling suggest that consumers make relatively little use of nutrition information, particularly if the information is complicated (Cowburn and Stockley 2005;Grunert and Wills 2007;Rex and Baumann 2007). Many researchers (e.g., Erskine and Collins 1997;Valor 2008;Weightman and McDonagh 2004) have reported that consumers are rarely influenced by claims of sustainability, but others have reported an increasing willingness to pay a premium for "green" products (Laroche et al 2001;Young et al 2010).…”
Section: Literaturementioning
confidence: 96%
“…For example, nutrition labels inform people about the nutritional benefits and costs afforded by a particular food item. In a similar manner, regulations in some areas require the provision of calorie information in restaurants [14,23]. These initiatives are designed to help people make informed decisions, and accordingly, the information is displayed in ways designed to be easy to find and easy to understand without special skills.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, it is natural for consumers to infer that consuming a product augmented with a functional claim either promotes health or reduces risk of developing disease. Though entirely comprehensible, these interpretations are-seen from the perspective of professional nutritionists-very often naïve and flawed (Cowburn and Stockley 2005;Gorton 2007;Grunert and Wills 2007;Mannell et al 2006;Williams 2005).…”
Section: Functional Claims: Ethical Challengesmentioning
confidence: 97%